The impact of disturbance intensity on spatial variability of habitat conditions and seedling recruitment of selected rare, medicinal plants in Molinion patches - Kostrakiewicz-Gierałt, Kinga (Ecological Questions, 2019)
The investigations were conducted in two Molinion patches dominated by small meadow species (ME) and overgrown by tall-growing macroforbs (MAC). Observations were carried out in systematically arranged permanent experimental plots divided in experimental subplots. The subplots were subjected to: I) no disturbances; II) low level of disturbance, corresponding with trampling consisting of the litter and moss layer removal; III) intermediate level of disturbance, corresponding with mowing consisting of the litter, moss, and above-ground part of plants removal; and IV) high level of disturbance, corresponding with rooting by wild mammals consisting of the litter, moss and the plants removal, as well as top soil raking with a metal scraper about 7 cm deep. The light availability was greater in Patch ME, while the soil humidity achieved higher values in Patch MAC. At the same time, the light availability increased in consecutive subplots, whereas the soil humidity showed a reversed trend. The cumulative number of seedlings Betonica officinalis and Succisa pratensis in Patches ME and MAC was similar, while Sanguisorba officinalis recruited more abundantly in Patch ME. The greatest number of offspring of all studied taxa was noticed in subplots III and IV. The obtained results might contribute to creating of succesful plans of enlargement of natural resources of medicinal plants in Molinia meadows-one of most valuable semi-natural communities in Europe.